2015
DOI: 10.1111/codi.12911
|View full text |Cite
|
Sign up to set email alerts
|

Adenomas with high‐grade dysplasia and early adenocarcinoma are more likely to be sessile in the proximal colon

Abstract: APNs in the proximal colon were almost four-times more likely to be sessile than those in the distal colon. No difference in the size of polyps was noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The issue of the "biology" of proximal versus distal lesions has been a matter of controversy; recent retrospective analyses have reported that proximally located adenomas with HGD were significantly smaller 19 or that proximal locations were associated with a higher rate of malignancy. 20 However, the present results are in line with those of other studies showing contradictory evidence: recurrence rates after polypectomy (a possible indicator for more aggressive biology) were equivalent or even lower in the proximal colon. 21,22 In addition, the mortality rate from CRC after polypectomy was not found to be higher with right-sided adenomas in the Norwegian cancer registry.…”
Section: Discussionsupporting
confidence: 92%
“…The issue of the "biology" of proximal versus distal lesions has been a matter of controversy; recent retrospective analyses have reported that proximally located adenomas with HGD were significantly smaller 19 or that proximal locations were associated with a higher rate of malignancy. 20 However, the present results are in line with those of other studies showing contradictory evidence: recurrence rates after polypectomy (a possible indicator for more aggressive biology) were equivalent or even lower in the proximal colon. 21,22 In addition, the mortality rate from CRC after polypectomy was not found to be higher with right-sided adenomas in the Norwegian cancer registry.…”
Section: Discussionsupporting
confidence: 92%
“…Research has suggested that molecular, pathological, and clinical features of colorectal neoplasia differ by anatomic location. 40 Sawhney et al 41 found that adenomas with high-grade dysplasia and early adenocarcinoma in the proximal colon were almost four times as likely to be sessile than those in the distal colon, though it has been reported that the prevalence of serrated adenomas was very low (0.9%) in a Chinese population. 15 The usual pathogenesis of colorectal cancer is an adenomatous polyp that slowly increases in size, followed by dysplasia and finally cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The European guidelines [45] recommended a more aggressive surveillance at 1 year for high risk polyps (≥ 20 mm). In the treatment with piecemeal resection, Walsh et al revealed a rate of 14% polyp recurrence after at least one negative examination, and the rate of CRC development was 17% in 65 patients with large at polyps [46]. A second look examination for patients who underwent piecemeal resection or suspected incomplete resection may be warranted.…”
Section: Discussionmentioning
confidence: 99%